Trajnostni promet v Prištini - Hoxha, Visar (Urbani izziv, 2023)
This study examines ineficiencies, possible improvements, challenges, and impacts of sustainable transportation alternatives in Prishtina with the goal of creating evidence-based strategies for small rapidly urbanizing cities and contributing to the knowledge about sustainable transportation in small and developing countries. The study uses a qualitative approach and semi-structured interviews with twelve participants to explore sustainable transportation in Prishtina, with thematic analysis and cross-case analysis to analyse the responses. The findings underscore significant ineficiencies in Prishtina’s transportation system, rooted in outdated infrastructure and varied stakeholder views. Through thematic and cross-case analyses, the study sheds light on the multifaceted challenges of implementing sustainable transportation. This study adds to the literature with insights into Prishtina’s context, offering actionable guidance for transportation planning specialists. For society, the results emphasize the imperative of a comprehensive approach, blending infrastructure enhancements with behavioural adaptations, to cultivate a sustainable urban milieu in Prishtina.
Keywords: infrastructure improvement; infrastrukturne izboljšave; javni prevoz; načrtovanje trajnostne urbane mobilnosti; public transport; sustainable urban mobility planning; trajnostna mesta